2022
DOI: 10.1021/acsnano.2c03613
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Nanodiamond Skin Permeation Profiling Using a Phase Analysis Method: Ex Vivo Experiments

Abstract: Carbon-based nanoparticles (NPs) are widely used in nanotechnology. Among them, nanodiamonds (NDs) are suitable for biotechnology and are especially interesting for skin delivery and topical treatments. However, noninvasive detection of NDs within the different skin layers or analyzing their penetration ability is complicated due to the turbid nature of the tissue. The iterative multiplane optical properties extraction (IMOPE) technique detects differences in the optical properties of the measured item by a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Thus, it appears that small molecule topical drugs have a greater need to limit the rate of transdermal absorption. Mineral-based materials, such as apatite, diamond and montmorillonite clay, are currently important in limiting the transdermal penetration of bioactive composition of drugs and maintaining local action ( Choimet et al, 2020 ; Shapira et al, 2022 ; Wang and Phillips, 2022 ). However, there are fewer studies of mineral-based materials in topical drug delivery systems, and the mechanism of action is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that small molecule topical drugs have a greater need to limit the rate of transdermal absorption. Mineral-based materials, such as apatite, diamond and montmorillonite clay, are currently important in limiting the transdermal penetration of bioactive composition of drugs and maintaining local action ( Choimet et al, 2020 ; Shapira et al, 2022 ; Wang and Phillips, 2022 ). However, there are fewer studies of mineral-based materials in topical drug delivery systems, and the mechanism of action is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Since the detection of the IMOPE technique is based on evaluating 𝜇 𝑠 ′ , detection of small NPs with negligible scattering poses a challenge for the IMOPE technique. We extend the technique for sensing nanodiamonds (ND) as such, by sensing the change of the root mean square (RMS) of the phase, difference caused by the ND's absorption [13]. First, we modify the theoretical model for absorption-oriented analysis and present measurements of solid and liquid intralipid (IL) phantoms that agree with our theoretical model.…”
Section: Introductionmentioning
confidence: 89%
“…First, we modify the theoretical model for absorption-oriented analysis and present measurements of solid and liquid intralipid (IL) phantoms that agree with our theoretical model. We applied NDs solution on ex vivo pigskin and used the IMOPE to show the penetration of NDs along the three skin layers (epidermis, dermis and fat) [13,14]. Moreover, we showed that the significance signal of the NDs reduces along with the depth of the skin layer and presented values for the relative concentration of NDs in each layer-non-invasively.…”
Section: Introductionmentioning
confidence: 96%
“…They have a large surface area with a microscopic diameter between 2 and 8 nanometers. They are nanocrystals with a diamond-like structure which gives them particular electronic and physical properties [38] The fullerenes are spherical and resemble cages. Also known as buckminsterfullerene, it is a compound with a spheroidal polyhedral structure with 60 carbon atoms.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%